Apakah Metode Project Based Learning Dapat Meningkatkan Keterampilan Menulis Siswa di Masa Pandemi Covid-19? - Triznaroza Triznaroza (Jurnal Bahasa dan Sastra, 2021)
Student’s writing skill is an important aspect of linguistic ability, yet many students develop a poor interest in writing skill. The Classroom Action Research is based on the low ability of student’s writing skills. For that reason through the method of project based learning, it is expected that student’s writing skills should increase. It was conducted at SMP Negeri 4 Manggar, during the covid-19 pandemic. This research used three cycles which each cycle consisting of two meetings with four stages (design, implementation, observation, and reflection). The data obtained were formative test results, student activeness observation sheets, teaching and learning activities and questionnaires. The results showed that student learning rate of each cycle had increased. The percentage of classical completeness in first cycle was 53%, second cycle was 73%, and third cycle was 93%. The student activeness in the teaching and learning process in first cycle was 65%, second cycle was 83%, and third cycle was 92%. Overall it can be concluded that the Project Based Learning method can improve the writing skills ability of class VIII-A1 students of SMP Negeri 4 Manggar.